An inquiry into factors affecting the online learning experiences of A-level chemistry students studying in a blended learning course in a college in Malta and the impact of these experiences on learning identity - Role, Sharon Joan (2014)
This study carried out as practitioner-research explores the new online collaborative learning experiences of a class of thirty-seven college students studying A-level chemistry in a blended learning context. It is a case-study with a multi-method interpretivist approach using observations, unsolicited meetings, VLE tracking system, students’ reflective journal, online informal discussions, questionnaires, focus groups and individual interviews. The students, used to traditional non-collaborative learning methods in the face-to-face class, demonstrated complex online behaviour patterns. Findings showed that the factors affecting these behaviours were of a situational, infrastructural and persona-related nature. Four key learning dispositions – resourcefulness, resilience, reciprocity and responsibility were identified as persona-related enablers. These dispositions were instrumental for changes in the students as learners. These included changes in epistemological beliefs, study patterns, study habits and above all, in learner roles and learning identities. Notable changes occurred in a group of learners who were initially reluctant to learn from the online environment. This study suggests that online learning can not only support a socio-constructive approach to learning to students in the online setting, but also induces similar student learning behaviours in the face-to-face class. The study also gives evidence of transformation in the academic and the positional student learning identities. The new interacting student learning identities projected a sense of belonging, of being valued and of connectedness in both the online and the face-to-face class community. This research is significant as a study of the impact of online experiences on college students in a blended learning context. Similar research contexts were scarce in the literature. It is valuable to the current teaching community in Malta, where the recent National Curriculum Framework (2012) has emphasised a socio-constructive approach to learning and where several educational institutions have started using VLEs to provide blended learning experiences.